Regulatory Effect of γδ T Cells on IL-17(+) Uveitogenic T Cells - Nian, Hong (Association for Research in Vision and Ophthalmology, Inc., 2010)
PURPOSE. To characterize the regulatory effect of γδ T cells in the activation of IL-17(+) uveitogenic T cells. METHODS. The authors administered the γδ TCR-specific antibody GL3 to B6 mice before or after antigen immunization and examined Th1- or Th17-polarized T-cell responses. The intensity of Th17 responses was also examined in responder T cells containing varying numbers of γδ T cells. RESULTS. GL3 treatment resulted in varying degrees of depletion of circulating γδ T cells, depending on when the antibody was administered. The intensity of the αβTCR(+)IL-17(+), but not the αβTCR(+)IFN-γ(+), IRBP-specific T-cell responses was correlated to the percentage of γδ T cells in the responder T cells. Kinetic studies showed that early IL-17(+) T cells were primarily γδ T cells, with a later gradual shift to αβ T cells. A close association was seen between the intensity of the IL-17(+) autoreactive T-cell response and the percentage of γδ T cells in the responder T cells. Although a modest increase in γδ T cells among the responder T cells promoted the expansion of IL-17(+) αβTCR(+) T cells, a higher proportion of γδ T cells inhibited it. CONCLUSIONS. γδ T cells are actively involved in the generation of αβTCR(+)IL-17(+) T cells. The number of γδ T cells and the αβ/γδ T-cell ratio in the responder T cells regulate the intensity of the Th17-type autoreactive T-cell response.